Analyzing empirical notions of suffering: Advancing youth dialogue in Hindu and Christian perspectives - Baring, Rito V. (Animo Repository, 2008)
This paper explores the possibilities of advancing inter-faith dialogue among the youth using empirical notions of students on suffering as the subject of analysis and discussion. It examines the contributions of empirical data towards efforts intended for Hindu-Christian dialogue. Within this attempt, relevant Hindu-Christian perspectives shall be reviewed and an outline of the Filipino youth's notions of suffering shall be described. Using empirical data, the Christian proposition to the problem of suffering will be examined viz a viz the Hindu appreciation of the human experience. Through an analysis of insights coming from these traditions, implications for youth inter-faith dialogue between the two religious traditions shall be explored.